Vertical green system for gray water treatment: Analysis of the VertiKKA-module in a field test - Aicher, Andreas; Boermel, Melanie; Londong, Jörg; Beier, Silvio (Frontiers in Environmental Science, 2022)
This work presents a modular Vertical Green System (VGS) for greywater treatment, developed at the Bauhaus-Universität Weimar. The concept was transformed into a field study with 4 modules build and tested with synthetic greywater. Each module set contains a small and larger module with the same treatment substrate and was fed hourly. A combination of lightweight structural material and biochar of agricultural residues and wooden chips were used as treatment substrate. In this paper we present the first 18 weeks of operation. Regarding the treatment efficiency the parameter Chemical Oxygen Demand (COD), Total Phosphorous (TP), ortho-Phosphate (ortho-P), Total bound Nitrogen (TNb), ammonium nitrogen (NH4-N) and nitrate nitrogen (NO3-N) were analyzed and are presented in this work. Results of the modules with agricultural residues are promising. Up to 92% COD reduction are stated in the data. Phosphate and nitrogen fraction are reduced significantly in these modules. By contrast, the modules with wooden chips reduces only 67 % of the incoming COD and respectively less of Phosphate and nitrogen fraction.